The Mediating Effect of Innovation on The Relationship between Strategic Management Dimensions and Construction Project Development: A Conceptual Framework - Al-Ali, M.S.M.; Musa, H. (International Journal of Human and Technology Interaction (IJHaTI), 2019)
Innovation becomes a crucial factor to the project development; a factor which is ignored by the previous strategic management models that focused more on the physical resources of the project. This paper aims to investigate the improvement of the linkage in between the competitive advantages’ roots and the projects’ development. A comprehensive review has been done wherein several previous strategic management models are discussed. The reviews found out that there are some pillars of strategies that contribute to the project development. Even more, this review focuses on how to strengthen the direct relationship between the competitive advantages’ roots and the project development. This paper is significantly important because it adds innovation factor as a mediator between the competitive advantages and the project’s development. Hence, this paper provides an effective project development model linkage for the project’s strategic plan. Keywords—Competitive advantages; resources; value; capability; innovation; project development